Three new species of parasitoid wasps of the genus Mnioes Townes, 1946 (Ichneumonidae: Banchinae) in a humid forest in Peru - Ballon-Estacio, Ricardo; Alvarado, Mabel (Zootaxa, 2024)
Mnioes is a predominantly Neotropical genus of Banchinae (Ichneumonidae), currently including 26 species. Three new species of Mnioes are described, found in a humid montane forest in southern Peru, M. chunka sp. nov, M. chusaq sp. nov. and M. isqun sp. nov, and the male of M. huk Alvarado 2020 is also described. DNA barcoding for all the species treated here is included and provides information to match females with males, especially for M. chunka sp. nov., M. chusaq sp. nov., and M. soqta Alvarado 2020 where females are similar to each other and occur in sympatry. Additionally, an updated key to the Peruvian species is provided.